Human Development: Beyond the HDI - Gustav Ranis; Frances Stewart; Emma Samman (Yale University, Economic Growth Center, 2005)
This paper explores ways of enlarging the measurement and understanding of Human Development (HD) beyond the relatively reductionist Human Development Index. From the extensive literature on well-being, we derived eleven categories of HD. Within each category, we then identified a potential set of indicators which were measurable and reflect performance with respect to that category. In order to reduce the number of indicators representing each category, we included only one for any set highly rank order correlated with each other, as well as including indicators not correlated with any other indicator in that category. Our aim was to retain only indicators which are broadly independent of each other.
Keywords: I31; O15; O57; 330; Human Development; Quality of Life; Comparative Country Performance; Entwicklungsindikator; Lebensqualität; Entwicklungsländer